Analisis Semiotika Sosial M.A.K. Halliday Novel Ghoky Aku Papua Karya Johan Gandegoay - Insum Malawat (Badan Pengembangan dan Pembinaan Bahasa, 2023)
This research aims to describe and interpret the social and cultural symbols of the language used in the novel Ghoky Aku Papua by Johan Gandegoay as the subject. The research objects are the discourse field, discourse actors, and discourse means. The method used is Halliday's social semiotics content analysis model. Data collection techniques include (1) reading the GAP novel; (2) write the speeches of the characters which contain elements of discourse fields, discourse participants, and discourse means; and (3) classification of data in the form of clauses into tables containing discourse fields, discourse participants, and discourse means. Data analysis techniques are as follows. Identify and interpret signs and symbols that describe Papuan identity; describe and interpret the speech of the characters which represent the Papuan social context; and identifying and interpreting the speech of characters that represent language variations or styles. Based on the results of text analysis, it is concluded as follows. The discourse field in the novel GAP displays the socio-cultural environment of the Papuan people in coastal areas. The character highlighted regarding the identity of coastal people is open and communicative with various levels of society, both OAP and non-OAP. The language symbols that mark the Papuan social context are marked by Papuan dialects such as ko (you), pace (adult man), paitua (father), bitter melon fish tail, penggayu feet, and stilt houses as the identity of coastal communities. This component is present to represent the function of ideational metalanguage. Discourse involvement is shown through the presence of figures and their role as representatives of the socio-cultural community of the Papuan people and agents of change. This section reflects on the interpersonal function of language. Components of discourse means are displayed through the use of language styles, including metaphor, personification, polysynthesis, hyperbole, rhetoric, hypocorism and repetition. The means of discourse present represent the textual function of language. AbstrakPenelitian ini bertujuan menggambarkan dan memaknai simbol-simbol sosial budaya bahasa yang digunakan dalam novel Ghoky Aku Papua karya Johan Gandegoay sebagai subjek. Objek penelitian adalah medan wacana, pelibat wacana, dan sarana wacana. Metode yang digunakan adalah semiotika sosial Halliday model analisis isi. Teknik pengumpulan data meliputi (1) membaca novel GAP; (2) menuliskan tuturan dari para tokoh yang mengandung unsur medan wacana, pelibat wacana, dan sarana wacana; dan (3) klasifikasi data berbentuk klausa ke dalam tabel yang berisi medan wacana, pelibat wacana, dan sarana wacana. Teknik analisis data sebagai berikut. Mengidentifikasi dan memaknai tanda-tanda dan simbol-simbol yang menggambarkan identitas kepapuaan; menggambarkan dan memaknai tuturan para tokoh yang merepresentasikan konteks sosial kepapuaan; dan mengidentifikasi dan memaknai tuturan para tokoh yang melambangkan variasi atau gaya bahasa. Berdasarkan hasil analisis teks, disimpulkan sebagai berikut. Medan wacana dalam novel GAP menampilkan lingkungan sosial budaya masyarakat Papua di wilayah pesisir. Karakter yang ditonjolkan terkait identitas orang pesisir adalah terbuka dan komunikatif dengan berbagai lapisan masyarakat, baik OAP maupun non-OAP. Lambang bahasa yang menandai konteks sosial kepapuaan kepapuaan ditandai dengan dialek Papua seperti ko (kamu), pace (pria dewasa), paitua (bapak), ekor ikan pare, kaki penggayu, dan rumah panggung sebagai identitas masyarakat pesisir pantai. Komponen ini hadir mewakili fungsi metabahasa ideasional. Pelibat wacana ditunjukkan melalui kehadiran para tokoh dan perannya sebagai wakil komunitas sosial budaya masyarakat Papua dan agen perubahan. Bagian ini merefleksikan fungsi interpersonal bahasa. Komponen sarana wacana ditampilkan melalui penggunaan gaya bahasa antara lain metafora, personifikasi, polisindeton, hiperbola, retorik, hipokorisme, dan repetisi. Sarana wacana hadir mewakili fungsi tekstual bahasa.